The Use of ICT as a Resource and Media for Modern 21st Century Learning in Primary Schools - Prihantini, Prihantini; Sutarto, Sutarto; Punggeti, Ratna Novita; Rukmini, Ai; Intes, Amina (Journal International of Lingua and Technology, 2024)
The advancement of technology and information makes human life easier, but at the same time it makes some humans lack morals and behave badly due to lack of socialization. Behind all the bad impacts on the development of technology, there are also positive impacts in it, such as in the field of education. One of the positive impacts is ICT (Information and Communication Technology) learning media. The purpose of this study is to determine the use of ICT (Information and Communication Technology) as a Source and Media for Modern 21st Century Learning in Elementary Schools. This research uses quantitative methods, data obtained from distributing questionnaires and through interviews. The results of the study explain that the usefulness of ICT (Information and Communication Technology) as a source and modern learning media in elementary school children is very useful and helps students in carrying out learning. The conclusion of this study explains the usefulness of ICT (Information and Communication Technology) as a source and modern learning media in elementary school children is very helpful in the learning process. The researcher realizes the limitations of this study were only conducted in elementary schools in one of the districts in West Sumatra province, the researcher hopes that future researchers can conduct the same research with a wider range in order to continue this research. Researchers also recommend to researchers who will continue to be a benchmark in conducting research related to the use of ICT (Information and Communication Technology) as a modern learning resource and media in elementary schools.